J.K.ROULINGNING “BARD BIDL ERTAKLARI” ASARIDA QO‘LLANILGAN ALLITERATSIYALARNING SEMANTIK GURUHLANISHI VA ULARNI TARJIMA QILISH METOD VA USULLARI. (Journal of Universal Science Research, 2025)
This research analyzes examples of alliterations semantically as well as their translation methods and techniques found in “The Tales of Beedle the Bard” by J.K. Rowling.